2021
DOI: 10.1007/s00125-021-05630-0
|View full text |Cite
|
Sign up to set email alerts
|

The second-generation antipsychotic drug aripiprazole modulates the serotonergic system in pancreatic islets and induces beta cell dysfunction in female mice

Abstract: Aims/hypothesis Second-generation antipsychotic (SGA) drugs have been associated with the development of type 2 diabetes and the metabolic syndrome in patients with schizophrenia. In this study, we aimed to investigate the effects of two different SGA drugs, olanzapine and aripiprazole, on metabolic state and islet function and plasticity. Methods We analysed the functional adaptation of beta cells in 12-week-old B6;129 female mice fed an olanzapine- or ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Transferring preconceptionally isolated islets into a gestation-like state by incubation with high concentrations of 5-HT resulted in significant inhibition of insulin and glucagon secretion in NZO mice during stimulation with glucose. These observations are consistent with previous findings of other authors in MIN6 cells, rodents, and humans, although it should be noted that the influence of 5-HT on insulin secretion is still a matter of controversy [ 19 , 23 , 44 , 45 , 46 , 47 ]. An inhibitory effect on insulin secretion was also previously observed for the selective 5-HT re-uptake inhibitors (SSRIs) fluoxetine and sertraline in MIN6 cells as well as in mouse and human islets [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Transferring preconceptionally isolated islets into a gestation-like state by incubation with high concentrations of 5-HT resulted in significant inhibition of insulin and glucagon secretion in NZO mice during stimulation with glucose. These observations are consistent with previous findings of other authors in MIN6 cells, rodents, and humans, although it should be noted that the influence of 5-HT on insulin secretion is still a matter of controversy [ 19 , 23 , 44 , 45 , 46 , 47 ]. An inhibitory effect on insulin secretion was also previously observed for the selective 5-HT re-uptake inhibitors (SSRIs) fluoxetine and sertraline in MIN6 cells as well as in mouse and human islets [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been shown that treatment of female mice with the second-generation antipsychotic (SGA) drug aripiprazole elevated Tph1 and Tph2 expression and that 5-HT content in islets increased to a level comparable to pregnant mice. Moreover, treatment with aripiprazole led to a doubling of β-cell mass and further ex vivo experiments with the SGA resulted in impaired insulin secretion [ 45 ]. These findings are in close agreement with those obtained here in prediabetic NZO mice and suggest that blockade of peripheral 5-HT synthesis might lead to an improvement of impaired GSIS and thus to a reduced risk of the development of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that children treated with quetiapine have reduced insulin secretion (insulinogenic index) during an oral-glucose-tolerance test ( 37 ). Further, a recent study in a mouse model reported β-cell dysfunction, glucose intolerance, and impaired insulin secretion in female mice treated with aripiprazole ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that treatment of female mice with the SGA aripiprazole supplemented in the diet increased tryptophan hydroxylase 1 (TPH1) expression and serotonin production in pancreatic beta cells, causing beta cell dysfunction by interfering with the regulation of the serotoninergic system and also by inhibiting Ca 2+ entry [ 22 ]. However, using a similar administration route, olanzapine did not alter the expression of relevant genes related to insulin synthesis or islet function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our recent study we found that inhibition of insulin secretion in female mice receiving a chronic treatment with olanzapine seemed to be, at least in part, due to defective insulin granule maturation [ 22 ]. Amorphic insulin granules with reduced immunogold staining for mature insulin can reflect deficiencies in proinsulin processing at the ER, in which subsequent accumulation of misfolded proinsulin can exceed its functional capacity, thereby reducing insulin secretion [ 24 ].…”
Section: Discussionmentioning
confidence: 99%